Contribution of learning and knowledge technologies in the digital competences of students of higher basic education - Yoza, Aracely (2021)
This research covers the results of the use of learning and knowledge technologies (LKT). Its objective was to recognize the effects of the application of ICTs in the digital competencies of students in higher basic education at the José María Santana Salazar educational unit in Ecuador from December 2020 to July 2021. The methodology used was a mixed qualitative-quantitative approach, the research was descriptive, the population consisted of teachers and students of the higher sub-level, the sample was selective. Surveys and an interview with an expert provided specific information. The results highlight those teachers believe that they have knowledge on this subject in 38% and consider that students do not have digital competencies in terms of information management and security in 75% and 85% respectively, at the same time they value its importance within learning as an innovative aspect for their task; although their activities are developed without the effective application of these. It is concluded that the effects of the application of ICTs are positive in motivating classes, facilitating the subjects, promoting the attention and commitment of the students; however, the application of these tools is deficient due to the digital gap and the lack of training of teachers.